Performance of Mulberry Leaves Mediated Green Synthesis Zero-Valent Iron Nanoparticles in Dye Removal - Nie Lim, Sin; Ming Ng, Wei; Kang Lim, Jit; Xin Che, Hui (International Journal of Engineering and Technology, 2018)
The nanomaterials especially be made of iron, are tapering off the environmental pollution in a sufficiently great way which is worthy for attention. Green synthesis of iron nanoparticles through the extraction of the natural products or wastes has been developed in a way that is more sustainable than the chemical routes associated with several limitations. The mulberry leaves, which are easy available in nature, were chosen for plant-mediated green synthesis of zero-valent iron nanoparticles (nZVI). The characterization of the synthesized nanoparticles was performed with the used of dynamic light scattering (DLS), scanning electron microscope (SEM), and Fourier Transform Infrared Spectroscopy (FTIR). The polyphenols content of the mulberry leaf can be used to synthesize the iron nanoparticles. The iron nanoparticles can be used as the Fenton-like catalyst to enhance the efficiency of dyes degradation. Meanwhile, the iron nanoparticles can be removed by its magnetic properties after the degradation of pollutants which can be reused in subsequent environmental remediation. The efficiency of dyes degradation by the synthesized iron nanoparticles, was investigated by UV-visible spectroscopy (UV-vis). The cationic and anionic model dyes were used to investigate the ability of the synthesized iron nanoparticles in degradation of dye molecules. Methylene Blue was used as the model for cationic dye whereas Methyl Orange was chosen as anionic model dye. The percentage removal of respective dyes was investigated at the different period of time. The work investigated the magnetic and catalytic bi-functionalities of the synthesized iron nanoparticles.Â Â